Twenty Years of Education Transformation in Gauteng 1994 to 2014 - Maringe, Feliz; Prew, Martin (African Minds, 2015)
Twenty Years of Education Transformation in Gauteng 1994 to 2014: An Independent Review presents a collection of 15 important essays on different aspects of education in Gauteng since the advent of democracy in 1994. These essays talk to what a provincial education department does and how and why it does these things whether it be about policy, resourcing or implementing projects. Each essay is written by one or more specialist in the relevant focus area. The book is written to be accessible to the general reader as well as being informative and an essential resource for the specialist reader. It sheds light on aspects of how a provincial department operates and why and with what consequences certain decisions have been made in education over the last 20 turbulent years, both nationally and provincially. There has been no attempt to fi t the book's chapters into a particular ideological or educational paradigm, and as a result the reader will find differing views on various aspects of the Gauteng Department of Education's present and past. We leave the reader to decide to what extent the GDE has fulfilled its educational mandate over the last 20 years.